Massic Properties of the TE- Modes in a Lossless Waveguide - Erden, Fatih; Cosan, Ahmet A.; Tretyakov, Oleg A. (IEEE, 2018)
Analytical solutions of the TE-modal fields for a lossless waveguide are expressed within the framework of the evolutionary approach to electrodynamics (EAE). Electric and magnetic field vectors, which have physical dimensions of volt per meter and amper per meter respectively, are factorized in SI units. Elements of the modal basis that depend on transverse coordinates, r, and the modal amplitudes that depend on longitudinal coordinate, z, and time, t, are obtained via solving the boundary-eigenvalue problem. Exact solutions for mass and momentum are derived and presented graphically.
26th IEEE Signal Processing and Communications Applications Conference (SIU) -- MAY 02-05, 2018 -- Izmir, TURKEY
Keywords: Maxwell's equations; time-domain; waveguide; electromagnetics; Klein-Gordon equation; energy; mass; momentum